2016
DOI: 10.1152/ajpendo.00094.2016
|View full text |Cite
|
Sign up to set email alerts
|

Irisin exerts dual effects on browning and adipogenesis of human white adipocytes

Abstract: To better understand the role of irisin in humans, we examined the effects of irisin in human primary adipocytes and fresh human subcutaneous white adipose tissue (scWAT). Human primary adipocytes derived from 28 female donors' fresh scWAT were used to examine the effects of irisin on browning and mitochondrial respiration, and preadipocytes were used to examine the effects of irisin on adipogenesis and osteogenesis. Cultured fragments of scWAT and perirenal brown fat were used for investigating signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 50 publications
6
100
1
5
Order By: Relevance
“…In humans, irisin seems to induce WAT browning in specific types of adipocytes and fat depots 71 . Human preadipocytes from SAT demonstrate a decrease in differentiation to mature adipocytes after irisin treatment, whereas the expression of genes and/or proteins related to browning (for example, UCP1, PPARγ and PRDM16) remains unaffected or is even decreased 53,71,72 . Furthermore, irisin does not affect browning-related gene expression in human perirenal adipose tissue, which has high expression of UCP1 and is therefore considered to be BAT 72 .…”
Section: Effects On Glucose Homeostasismentioning
confidence: 99%
“…In humans, irisin seems to induce WAT browning in specific types of adipocytes and fat depots 71 . Human preadipocytes from SAT demonstrate a decrease in differentiation to mature adipocytes after irisin treatment, whereas the expression of genes and/or proteins related to browning (for example, UCP1, PPARγ and PRDM16) remains unaffected or is even decreased 53,71,72 . Furthermore, irisin does not affect browning-related gene expression in human perirenal adipose tissue, which has high expression of UCP1 and is therefore considered to be BAT 72 .…”
Section: Effects On Glucose Homeostasismentioning
confidence: 99%
“…It is known that brite adipocytes, converted from white adipocytes, exhibit properties of brown adipocytes like expression of UCP1 and a proposed mechanism for the induction of browning in WAT may occur by irisin derived from muscle after contraction (Bostrom et al 2012) or from the fat independent of physical exercise (Roca-Rivada et al 2013). A number of studies has demonstrated that the addition of exogenous irisin or irisin precursors (FNDC5) induced browning of white fat cells both in rodent (Zhang et al 2014; Bostrom et al 2012) and in human white fat cells (Zhang et al 2016; Huh et al 2014; Lee et al 2014). Fat cell browning in response to irisin treatment further induced cellular thermogenesis in mature human white fat cells (Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has demonstrated that the addition of exogenous irisin or irisin precursors (FNDC5) induced browning of white fat cells both in rodent (Zhang et al 2014; Bostrom et al 2012) and in human white fat cells (Zhang et al 2016; Huh et al 2014; Lee et al 2014). Fat cell browning in response to irisin treatment further induced cellular thermogenesis in mature human white fat cells (Zhang et al 2016). Because irisin may represent an early marker of fat cell browning and thermogenesis, it may have the potential as a novel anti-obesity drug (Bostrom et al 2012) or in a more general view could be seen as an attractive tool for the manipulation of energy metabolism in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Irisin is a recently discovered hormone and there is little evidence on factors that may modulate its signaling. Is well established in the literature that RT promotes irisin release, and also increases cellular thermogenesis and reduces fat storage by suppressing formation of new adipocytes [19,20,[39][40][41]. Therefore, maintaining optimal irisin concentrations seems to be important, especially in our ovariectomy model, which has strong evidences of being a precursor of obesity and other metabolic disorders [42][43][44][45].…”
Section: Ovariectomymentioning
confidence: 89%
“…We found that the Ovx-Sed group presented similar values of irisin levels when compared to Sham-Sed group (Figure 3). However, it is already known that irisin increases cellular thermogenesis by up regulating UCP1, thus it is important to analyze and consider the UCP1 concentrations in WAT [41,46].…”
Section: Ovariectomymentioning
confidence: 99%